Student Management In Developing Students' Emotional Intelligence - Muhammad Ashifudin; Ainur Rofiq (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
The focus of this research is such as (1) The planning of new students’ acceptance in the development of emotional intelligence of students at Kediri MTs. Ma’murotul Husna Middle School, (2) Classification of students in developing emotional intelligence of students at Kediri MTs. Ma’murotul Husna Middle School, (3) Implementation of student coaching in the development emotional intelligence of students at Kediri MTs. Ma’murotul Husna Middle School. This research if viewed from the sources of data, this study used primary and secondary data. While the type of data, the approach used includes qualitative research that produced the descriptive explanation. The technique of data collection in this study used three techniques, namely in-depth interview, participant observation, and study documentation. The data that has been collected is then analyzed in a parent's manner with three stages, namely: data reduction, data presentation, and drawing conclusion.The result of this research included: (1) Planning for admission of new students in the development of emotional intelligence in MTs. Ma’murotul Husna Middle School produces a plan for developing emotional intelligence of students, namely by having a policy regarding the acceptance of all prospective students who register either normal or children with especiality necessary. (2) The grouping of students in the development of emotional intelligence produced several parts which include class grouping based on the result of test that include children's learning abilitiy such as diagnostic test and IQ test, then there are extracurricular grouping based on talent and interest that exist in each student , and grouping learning to learn the method of Yanbu'a that are tailored to the ability of students. (3) The implementation of coaching there are three categories, namely disciplinary coaching that madethe students have emotional condition such as responsibility, academic coaching and non-academic coaching, each coaching is able to develop emotional students such as activities inside or outside classroom such as motivate themselves and responsible for carrying out these activities. Not only responsibility but also confidence, honesty, have empathy and foster good relations between the teachers and the fellow students..